Chemical Composition of the Essential Oil of Three Tanacetum Species from North-West of Iran (Journal of Medicinal Plants and By-products, 2012)
The genus Tanacetum is one of the most important medicinal plants that contains 26 species in Iran, 12 of them are endemic. This paper reports the essential oil composition of  Tanacetum angulatum Willd. Tanacetum canacens DC. and Tanacetum pinnatum Boiss. growing wild in Iran. Plant flowers and leaves were collected from different locations of North- West of Iran. Samples were hydro-distilled to produce the oils in the yields (v/w) of 0.4% for leaves and 0.02% for flowers for both T. angulatum Willdand T. canacens DC.,  collected from  Azerbaijan province (Tabriz), in of 0.05% for leaves and 0.2% for flowers T. pinnatum from Zanjan province (Zanjan) Main oil components of T. angulatum Willd.identified by GC/MS for leaves were 1,8-cineole (75.3%), camphor (8.1%) and for flowers were  1,8-cineole (66.0%), camphor (9.0%). For Tanacetum canacens, main oil components of leaves were 1,8-cineole (25.3%), α- calacorene (7.9%) and for flowers were n-eicosane (19.7%), α- calacorene (13.3%). Main oil constituents of T. pinnatum leaves were camphor (24.2%), α-calacorene (13.3%), and for flowers were germacrene B (33.0%), n-eicosane (10.5%).